USING TECHNOLOGY TO IMPROVE SPEAKING SKILLS IN INDONESIAN - Santi Rusmayanti; Iis Ristiani (Media Inovasi Pendidikan dan Publikasi, 2023)
Speaking skills in Indonesian have an important role in communication and education. This study investigated the use of mobile apps as a tool to improve speaking skills in Indonesian. Involving university students as participants, this study found that the use of mobile apps has a positive impact in improving speaking skills and self-confidence. Despite challenges such as accessibility, this study provides recommendations to maximize the benefits of technology in Indonesian speaking learning. The results of this study provide practical guidance for educators and students.